Arctic Biodiversity Trends 2010 – Selected indicators of change. - Arctic Council , Conservation of Arctic Flora and Fauna Working Group (CAFF International Secretariat, 2010)
In the past 100 years, average Arctic temperatures have increased at almost twice the average global rate [8]. Over the past thirty years, seasonal minimal sea ice extent in the Arctic has decreased by 45,000 km2/year. Along with earlier break-up and freeze-up, the extent of terrestrial snow cover in the Northern Hemisphere has decreased and is expected to continue to do so. The magnitude of these changes will exert major influences on biological dynamics in the Arctic. Some of the most rapid ecological changes associated with warming have occurred in marine and freshwater environments. Species most affected are those with limited distributions or with specialized feeding habits that depend on ice foraging.